Semi-real-time infrared thermography for detecting layering defects in plasters solidification within indoor environments - Wan, Ruizhuo; Zhao, Hao; Zhang, Qingrui; Zheng, Pengfei; Zhong, Zhaoyuan; Xue, Chengcheng; Huang, Liang (Frontiers in Materials, 2024)
In the solidification of plasters, promptly identifying layering defects is vital to cut down on later inspection and maintenance expenses. Traditional tapping for detecting defects, while widespread, is inefficient and can harm walls. Addressing these challenges, this study proposes an innovative method utilizing Infrared Thermal Imaging (IRT) for real-time detection of layering defects during the solidification phase. This method was applied within the first 48 hours following the application of two different plasters(Cement and Gypsum, mixed on-site as needed, not pre-dosed, and applied in a single layer), systematically examining the effects of plaster composition and environmental temperature conditions. The results showed that all preset defects were successfully identified. It was observed that larger defects are more readily detectable at a given thickness, and conversely, thicker defects are more discernible at a fixed size, with the dimension of the defect having a more pronounced impact on absolute contrast than its thickness. Notably, cement plaster exhibited two distinct temporal windows for defect detection, primarily influenced by environmental temperatures. In contrast, gypsum mortar presented two detection phases, with the initial phase being predominantly governed by the heat of hydration and the latter by ambient temperature conditions. The application of IRT technology in this research demonstrates its efficacy in accurately detecting layering defects during the solidification of plasters, thereby offering valuable insights and guidance for the application of plaster layers in real-world engineering scenarios.